Membaca Mindset Wirausaha: Analisis Determinan Minat Berwirausaha pada Mahasiswa Generasi Z - Andalangi Maatuil, Rexy; Maria Bungkaes; Deske Lin Djole; Chrystania Dodopo; Marsya Langi; Jindro Djojobo (Indo Publishing, 2025)
This study aims to deeply analyze the entrepreneurial mindset among Generation Z students and identify the main factors that drive their interest in entrepreneurship. Through a literature review approach, this research examines various academic sources, such as local and international journals, to formulate thinking patterns, internal factors, external factors, and the technological context that influence the entrepreneurial tendencies of this generation. The findings reveal that this mindset is formed by a combination of self-efficacy, desire for autonomy, family support, and entrepreneurial education environment. Furthermore, the advancement of digital technology has been proven to boost entrepreneurial spirit through access to information, new business opportunities, and an online environment that stimulates creativity and innovation. This research emphasizes that Generation Z's interest in entrepreneurship depends not only on personal traits but also on dynamic technological and educational conditions. These findings contribute theoretically to understanding the determinants of entrepreneurship in young generations and provide practical guidance for educational institutions and policymakers to design more appropriate entrepreneurship development programs.